2019
DOI: 10.3389/fcell.2019.00208
|View full text |Cite
|
Sign up to set email alerts
|

NOD Signaling and Cell Death

Abstract: Innate immune signaling and programmed cell death are intimately linked, and many signaling pathways can regulate and induce both, transcription of inflammatory mediators or autonomous cell death. The best-characterized examples for these dual outcomes are members of the TNF superfamily, the inflammasome receptors, and the toll-like receptors. Signaling via the intracellular peptidoglycan receptors NOD1 and NOD2, however, does not appear to follow this trend, despite involving signaling proteins, or proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 168 publications
(229 reference statements)
0
53
0
Order By: Relevance
“…They monitor both inflammation and apoptosis signaling pathways. These receptors expressed in many cell types, including immune cells (lymphocytes, macrophages, dendritic cells) and even epithelial cells [61]. It is observed that activation of cytosolic NLRs increased during aging and in many age-related diseases such as type 2 diabetes mellitus.…”
Section: Aging and Autophagymentioning
confidence: 99%
“…They monitor both inflammation and apoptosis signaling pathways. These receptors expressed in many cell types, including immune cells (lymphocytes, macrophages, dendritic cells) and even epithelial cells [61]. It is observed that activation of cytosolic NLRs increased during aging and in many age-related diseases such as type 2 diabetes mellitus.…”
Section: Aging and Autophagymentioning
confidence: 99%
“…In addition to innate immune response, NOD1 is also involved in the activation of the apoptosis signaling pathway through its interaction with the CARD domain of RIP2. RIP2 is considered to be an important component of the multiprotein signaling complex that mediates innate immune responses induced by the activation of NOD1 [29,30]. The abnormal expression of NOD1 and RIP2 has been associated with cell apoptosis and development of breast cancer and oral cancer [18,31].…”
Section: Discussionmentioning
confidence: 99%
“…sarcoidosis, rheumatoid arthritis, solid cancers, uveitis, neuropathic pain, and type 2 diabetes mellitus [6].…”
Section: Case Reportmentioning
confidence: 99%